2006
DOI: 10.1002/cncr.22264
|View full text |Cite
|
Sign up to set email alerts
|

Phase I clinical trial of bortezomib in combination with gemcitabine in patients with advanced solid tumors

Abstract: BACKGROUND.Bortezomib is the first proteasome inhibitor to show preliminary evidence of activity against solid tumors. Findings from preclinical studies prompted a Phase I trial to determine the maximum tolerated dose (MTD) and dose‐limiting toxicities (DLTs) of bortezomib in combination with gemcitabine in patients with recurring/refractory advanced solid tumors. The effect of gemcitabine on proteasome inhibition by bortezomib in whole blood was also investigated.METHODS.Bortezomib was administered as an intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…Drug sensitivity testing was done using WST-1 assay and direct cell count for Caco-2 and HRT-18 cells, at different times (24,48,72, and 96 h) and doses (range, 0.01-0.1 μmol/L) of bortezomib. These concentrations are within those achieved clinically in the plasma of patients treated with bortezomib (17). To screen for IC 50 values, an indirect measure of cell viability and proliferation was done by determination of the metabolic activity of cells with a colorimetric assay based on cleavage of the tetrazolium salt WST-1 by mitochondrial dehydrogenases (cell proliferation reagent WST1; Roche Diagnostics).…”
Section: Cell Culturesmentioning
confidence: 90%
“…Drug sensitivity testing was done using WST-1 assay and direct cell count for Caco-2 and HRT-18 cells, at different times (24,48,72, and 96 h) and doses (range, 0.01-0.1 μmol/L) of bortezomib. These concentrations are within those achieved clinically in the plasma of patients treated with bortezomib (17). To screen for IC 50 values, an indirect measure of cell viability and proliferation was done by determination of the metabolic activity of cells with a colorimetric assay based on cleavage of the tetrazolium salt WST-1 by mitochondrial dehydrogenases (cell proliferation reagent WST1; Roche Diagnostics).…”
Section: Cell Culturesmentioning
confidence: 90%
“…Studies using bortezomib (PS-341), also a proteasomal inhibitor that inhibits NF-B activation, have demonstrated enhanced sensitization to radiation therapy in the LOVO xenograft model (98), increased chemosensitivity to CPT-11 in colorectal cancer cells (99), and enhancement of the cytotoxic effect of several chemotherapeutic agents including carboplatin and CPT-11 in glioma cells (100). Recently, phase I studies using bortezomib in combination with irinotecan (101) or with gemcitabine (102) or with capecitabine and L-OHP (103) in patients with advanced solid tumors have shown that these drug combinations are safe, with manageable toxicities, and are currently in Phase II trials, indicating that inhibition of NF-B may play an important role in new developmental therapeutic approaches in cancer. Although very recently Hideshima et al (104) showed that bortezomib and other proteasome inhibitors can also induce canonical NF-B signaling in MM cells through phosphorylation of receptor-interacting protein 2 as well as IKK␤ (105), which clearly indicates that the action of bortezomib and other proteasome inhibitors is not limited to NF-B inhibition and that other mechanisms may play a role in its anti-tumor activity.…”
Section: Discussionmentioning
confidence: 99%
“…These agents inhibit the degradation of multiubiquitinated target proteins, i.e., cell cycle regu- Bortezomib is the first proteasome inhibitor that has been introduced into clinical practice for the treatment of relapsed multiple myeloma, 2,28,47,48 and active clinical investigation is ongoing in other malignancies. [49][50][51][52][53][54][55] In this study we provide the framework for more intensive clinical investigation of bortezomib in AML. MTT uptake experiments on AML cell lines, sensitive and resistant to conventional chemotherapeutic agents, indicate that bortezomib is efficient at concentrations in the low nanomolar range, within pharmacologically achievable doses.…”
Section: Discussionmentioning
confidence: 99%